Construction of antibody-like nanoparticles for selective protein sequestration in living cells1. Issue 16 (28th April 2015) - Liu, Yibin; Fang, Simin; Zhai, Junqiu; Zhao, Meiping
<x xml:space="preserve">Abstract</x> Antibody-like nanoparticles enabled selective protein sequestration in living cells.